Identifying and Targeting the Cause of Cancer is Needed to Cure Cancer - Adjiri, Adouda (Oncology and Therapy, 2016)
Cancer cells continue to challenge scientists and oncologists due to the phenomenon of resistance. Moreover, recurrence, as seen in many treated patients, shows that currently-used anti-cancer drugs are unable to prevent the development of new cancer cells harboring new mutations. The purpose of this paper is to try to answer some of the questions regarding why cancer arises and why evolution would naturally lead to the development of cancer. Providing answers to these questions may shed new light on cancer development and potential causes of cancer. This work demonstrates that (1) cancer hallmarks are a series of events that can be organized in three consecutive stages; (2) cancer may develop when cells seek immortality; (3) heterogeneity in tumors may be explained by cancer cells not following universal laws for division; (4) evolution may not have selected for cancer; (5) currently-used anti-cancer drugs, with telomerase and poly adenosine diphosphate ribose polymerase inhibition given as examples, show that we may not be on the right track, as these drugs are probably targeting molecular symptoms of tumors but not their cause; and (6) after an attempt to define the cause of cancer, the potentials of immunotherapy are discussed. Future anti-cancer drugs should be able to shrink the original tumor(s) and most importantly prevent the rise of new cancer cells in treated patients. In order to achieve this goal, new drugs must target the cause of cancer. Therefore, future research must focus on identifying potential causes of cancer common to all types of cancers. Finally, while immunotherapy holds great prospects for future cancer cure and prevention, global action is needed to reduce harmful substances known to contribute to the development of cancer in the environment.